2011
DOI: 10.1557/jmr.2011.111
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of residual stresses in Al film/silicon nitride substrate microcantilever beam systems

Abstract: Microcantilevers fabricated by microelectromechanical system processes were used to study the residual stresses in the film/substrate systems. Aluminum films were deposited on silicon nitride substrates by thermal evaporation at room and elevated temperatures, and residual stresses were characterized from the deflection profiles of the Al/SiN x microcantilevers. The Al/SiN x microcantilever beam made of room-temperature-deposited Al film was found to deflect toward the substrate side, which in turn resulted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Instead of observing its electrical properties, it also becomes necessary to study its morphology and residual stress since they will affect the functional properties. C. C. Lin, et al who studied residual stress in Al film deposited on Si 3 N 4 substrate reported that room-temperature-deposited Al film had compressive residual stress in the film, while the residual stresses of Al film deposited at 105 °C were tensile [6]. J. H. Lee, et al who studied the mechanical properties of Al/AlN multilayer thin films, reported that measurement result on residual stress showed Al layers were subjected to compressive stress which was induced by the interface which caused overall increase of the compressive stress in the multilayer thin films [7].…”
Section: Introductionmentioning
confidence: 99%
“…Instead of observing its electrical properties, it also becomes necessary to study its morphology and residual stress since they will affect the functional properties. C. C. Lin, et al who studied residual stress in Al film deposited on Si 3 N 4 substrate reported that room-temperature-deposited Al film had compressive residual stress in the film, while the residual stresses of Al film deposited at 105 °C were tensile [6]. J. H. Lee, et al who studied the mechanical properties of Al/AlN multilayer thin films, reported that measurement result on residual stress showed Al layers were subjected to compressive stress which was induced by the interface which caused overall increase of the compressive stress in the multilayer thin films [7].…”
Section: Introductionmentioning
confidence: 99%